Propaganda intelligence and covert action: the Regional Information Office and British intelligence in South-East Asia, 1949-1961. Issue 1 (2nd January 2020) - Shaw, Alexander Nicholas
ABSTRACT: This article explores the intersections between propaganda, intelligence and covert action through the experience of Britain's Regional Information Office (RIO) in Singapore. RIO defined its functions as 'propaganda intelligence': the generation of intelligence to guide propaganda output and analysis of enemy propaganda to feed into the broader intelligence picture of communist intentions. This highlights the interdependency of intelligence and propaganda. RIO worked closely with MI5 and MI6 in developing intelligence on communist China and North Vietnam. Evaluating the position of RIO within Britain's regional intelligence network also reveals some of the complexities of the late-imperial intelligence system. It illuminates the changing status of different intelligence activities and the growth of a particular intelligence culture, providing insight into how Britain engaged with the clandestine Cold War in South-East Asia.